Effect of ethylene and 1-methylcyclopropene on the postharvest behavior of cape gooseberry fruits (2020)
Cape gooseberry (Physalis peruviana L.) fruits are highly perishable berries that exhibit a climacteric respiratory behavior. The objective of this study was to evaluate the effect of ethylene and the ethylene action inhibitor 1-methylcyclopropene on the postharvest behavior of cape gooseberry fruits (ecotype Colombia). Fruits were treated with ethylene, in an ethephon application (1000 µL L−1), and pretreated with 1-methylcyclopropene (1 µL L−1), 1-methylcyclopropene+ethylene, and results compared with a control without application. Subsequently, the fruits were maintained at room temperature (20 ℃, 75% RH) for up to 11 days. The pretreatment of the cape gooseberry fruits with 1-methylcyclopropene delayed most of the ripening-associated parameters, with a reduction in the respiration rate and ethylene production, skin color development, total soluble solids, total carotenoid content, loss of firmness, loss of total titratable acidity and emission of volatile compounds such as ethyl octanoate, ethyl butanoate, ethyl decanoate, and hexyl decanoate. Conversely, application of ethephon accelerated most of these physiological changes and also overcame most of the effects prevented by the ethylene action inhibitor. Altogether, the results supported the idea of a climacteric-like behavior for cape gooseberry fruits and pointing out that the pretreatment with 1-methylcyclopropene may be a promising and efficient postharvest treatment to delay maturity and extend the postharvest period.